2019
DOI: 10.1029/2018jb016803
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Nucleation Size: Evidence of Loading Rate Dependence in Laboratory Faults

Abstract: Recent Global Positioning System observations of major earthquakes such as the 2014 Chile megathrust show a slow preslip phase releasing a significant portion of the total moment (Ruiz et al., 2014, https://doi.org/10.1126/science.1256074). Despite advances from theoretical stability analysis (Rubin & Ampuero, 2005, https://doi.org/10.1029/2005JB003686; Ruina, 1983, https://doi.org/10.1029/jb088ib12p10359) and modeling (Kaneko et al., 2017, https://doi.org/10.1002/2016GL071569), it is not fully understood what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 49 publications
(101 reference statements)
10
50
0
1
Order By: Relevance
“…From equation (4), we would expect h * to remain relatively constant in a given sequence as long as the normal stress, rigidity of the fault rocks, and friction properties remain constant, but recent experiments have shown that h * can vary based on loading rate, healing time, and other factors (Guérin‐Marthe et al, ; McLaskey & Yamashita, ). In particular, h * has been shown to shrink in response to “kicks” such as after sudden increases in loading rate or upon resumption of loading after holding periods where the fault is held in essentially stationary contact.…”
Section: Discussionmentioning
confidence: 99%
“…From equation (4), we would expect h * to remain relatively constant in a given sequence as long as the normal stress, rigidity of the fault rocks, and friction properties remain constant, but recent experiments have shown that h * can vary based on loading rate, healing time, and other factors (Guérin‐Marthe et al, ; McLaskey & Yamashita, ). In particular, h * has been shown to shrink in response to “kicks” such as after sudden increases in loading rate or upon resumption of loading after holding periods where the fault is held in essentially stationary contact.…”
Section: Discussionmentioning
confidence: 99%
“…The USGS 2-m block is likely somewhat rougher than others, while Onaka and Kuwahara, (1990) is smoother. Variability due to loading rate effects is shown inKato et al (1992) andGuérin-Marthe et al (2019).…”
mentioning
confidence: 99%
“…Similarly, normal stress concentrations in the direct shear experiments form at one or both ends, as observed from strain gauge measurements (Bayart et al, 2016;Ben-David et al, 2010), pronounced fault wear (Mclaskey & Yamashita, 2017), pressure sensitive films (Yamashita et al, 2018), and modeling (Kammer et al, 2015). The distribution of the shear and normal stresses along the experimental faults is furthermore affected by other geometrical factors and boundary conditions, such as the sizes of the PMMA blocks with respect to each other, whether shear loading is applied uniformly or at a point (Bayart et al, 2016), the location at which the shear load is applied (Ben-David et al, 2010), deformation of the frame containing the experimental setup (Ke et al, 2018) and whether motion is allowed between hydraulic presses and the forcing blocks (Guérin-Marthe et al, 2019;Langer et al, 2013). Depending on the relative magnitude of the shear and normal stresses, maxima in τ/σn will form at some distance from the fault end(s) (e.g.…”
Section: 1 1 Effect Of Experimental Boundary Conditions On Fault mentioning
confidence: 99%
“…When the nucleation length is close to the laboratory fault length, the mode of fault sliding (seismic vs. slow or aseismic slip) can be controlled by changing the loading conditions such as the normal stress (Mclaskey & Yamashita, 2017). Both experimental (Guérin-Marthe et al, 2019;Kato et al, 1992;Xu et al, 2018) and numerical (Kaneko et al, 2016, Kaneko & Lapusta, 2008 studies further show that the nucleation length decreases with increasing loading rate, whereas it increases with fault roughness (Ohnaka & Shen, 1999;Yamashita et al, 2018).…”
mentioning
confidence: 98%
See 1 more Smart Citation